Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-74087-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Membrane Components–A Proteomic Approach

Abstract: The milk fat globule membrane (MFGM) is the membrane surrounding lipid droplets during their secretion in the alveolar lumen of the lactating mammary gland. MFGM proteins represent only 1-4% of total milk protein content; nevertheless, the MFGM consists of a complex system of integral and peripheral proteins, enzymes, and lipids. Despite their low classical nutritional value, MFGM proteins have been reported to play an important role in various cellular processes and defense mechanisms in the newborn. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 28 publications
2
72
0
Order By: Relevance
“…The origin of the MFGM and the mechanism of cellular milk fat secretion continue to be areas of intense investigation. Proteomic approaches have identified many of the associated proteins (Reinhardt and Lippolis, 2006;Cavaletto et al, 2008), and knock-out mouse models have demonstrated the essential role for some of these proteins in milk fat secretion including butyrophilin (Ogg et al, 2004) and xanthine oxidoreductase (McManaman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the MFGM and the mechanism of cellular milk fat secretion continue to be areas of intense investigation. Proteomic approaches have identified many of the associated proteins (Reinhardt and Lippolis, 2006;Cavaletto et al, 2008), and knock-out mouse models have demonstrated the essential role for some of these proteins in milk fat secretion including butyrophilin (Ogg et al, 2004) and xanthine oxidoreductase (McManaman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The milk fat globule membrane (MFGM) is the structural membrane covering triglyceride globules that are dispersed as emulsified bodies in milk (9), and it is prepared from buttermilk by filtration and centrifugation (10). The MFGM contains unique polar lipids and membrane-specific proteins (9), and several nutritional benefits of MFGM components, such as anti-cancer and anti-cholesterolemic effects, have been reported (11).…”
mentioning
confidence: 99%
“…The MFGM contains unique polar lipids and membrane-specific proteins (9), and several nutritional benefits of MFGM components, such as anti-cancer and anti-cholesterolemic effects, have been reported (11). However, the efficacy of MFGM for physical function is not fully understood.…”
mentioning
confidence: 99%
“…Considering the nutraceutical and biological significance of these proteins, currently there is an increased interest in MFGM [14]. Despite MFGM proteins making up only 1-4% of the total milk protein content, it is a protein family that shows a greater complexity than other fractions in milk [15,16]. The significance of MFGM proteins has been surveyed and examined by researchers, especially their bioactivities [17,18].…”
Section: Introductionmentioning
confidence: 99%